2000
DOI: 10.1021/om0002024
|View full text |Cite
|
Sign up to set email alerts
|

Transmetalation as a Route to a Cyclic Heteronuclear Bifunctional Lewis Acid Containing Tin and Gallium

Abstract: The reaction of equimolar quantities of 1,8bistrimethylstannylnaphthalene (1) and GaCl 3 in toluene yields a stannagallacycle, namely, bis(µ-1,8-naphthalenediyl)(µ-chloride)methyltin(IV)chlorogallium(III) (2). Compound 2 is insoluble in solvents of low polarity and has been characterized by EA, MSCI, and X-ray analysis. The latter revealed the existence of a folded eightmembered dimetallacycle as well as the presence of a chloride ligand bridging the two metals. When treated with pyridine, formation of a solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The second pyridine molecule may either coordinate to the Lewis acidic tin group or to boron thus replacing chloride under formation of a boronium cation. Coordination of pyridine to tin has, for example, been recently reported by Gabbaï and co‐workers for a heteronuclear bifunctional Lewis acid featuring tin and gallium atoms adjacent to each other 39. Formation of boronium cations from organoboron halides on the other hand is a common process,40 and we indeed found that the monofunctional Lewis acid [FcB(Cl)Me] readily forms a boronium cation with two equivalents of pyridine (see vide infra).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The second pyridine molecule may either coordinate to the Lewis acidic tin group or to boron thus replacing chloride under formation of a boronium cation. Coordination of pyridine to tin has, for example, been recently reported by Gabbaï and co‐workers for a heteronuclear bifunctional Lewis acid featuring tin and gallium atoms adjacent to each other 39. Formation of boronium cations from organoboron halides on the other hand is a common process,40 and we indeed found that the monofunctional Lewis acid [FcB(Cl)Me] readily forms a boronium cation with two equivalents of pyridine (see vide infra).…”
Section: Resultssupporting
confidence: 72%
“…Steric congestion around tin results in rotation of the stannyl moiety thereby providing maximum space for the two axial chloride ligands. However, significant steric strain in the zwitterion 7 is still encountered as reflected in a strong upward tilt of the stannyl group of 11.7° relative to the Cp plane as well as strong distortions of the angles C(2)‐C(1)‐Sn(1) of 134.5(3)° and C(5)‐C(1)‐Sn(1) of 117.0(3)° between tin and the Cp ring (undistorted angle: 126°) 45. The Sn–Cl(2) distance of 2.7827(12) Å is significantly longer than that observed for Sn–Cl(1) of 2.5549(13) Å.…”
Section: Resultsmentioning
confidence: 99%
“…When using a bulkier radical, such as 2,4,6-trisisopropylphenyl (Trip), instead of Mes in the starting nickel complex, [NiBr(Ar)(PPh 3 ) 2 ], the formation of a product analogous to {dmit(Mes)} 2 ({dmit(Trip)} 2 , 5) occurs, but as the major product of the reaction. Although [Ni(dmit)(PPh 3 )] 2 (1) is obtained as well, the related thiolate thioether derivative (3) [Ni(Trip)(dmitTrip)(PPh 3 )] is not, probably as a consequence of steric factors.…”
Section: Resultsmentioning
confidence: 99%
“…Upon addition of pyridine, both Lewis acidic metals are independently coordinated. 27 In related studies, Gabbai and coworkers showed the same 1,8-bis(trimethylstannyl)naphthalene precursor can be transmetalated with indium trichloride to yield a dimeric indium macrocycle. The reported diindacycle synthesized by transmetalation is isolated in 65% yield, whereas metathesis of a 1,8-dilithionaphthalene with InCl 3 and tmeda gives the diindacycle in only 25% yield by NMR spectroscopy.…”
Section: Supramolecular Transmetalation: Direct Exchangementioning
confidence: 99%